2021
DOI: 10.1212/nxi.0000000000001011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Maternal-to-Fetal Transfer of IgG Antibodies by FcRn Blockade in a Mouse Model of Arthrogryposis Multiplex Congenita

Abstract: ObjectiveTo determine whether blocking the neonatal Fc receptor (FcRn) during gestation with an anti-FcRn monoclonal antibody (mAb) reduces transfer of pathogenic maternal antibodies in utero and decreases the likelihood of maternal antibody-mediated neonatal disease in the offspring.MethodsUsing a previously established maternal-to-fetal transfer mouse model of arthrogryposis multiplex congenita (AMC), we assessed the effect of 4470, an anti-FcRn mAb, on the transfer of total human immunoglobulin G (IgG) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…Such transfer occurs in alloimmune and IgG-mediated autoimmune diseases, and in these instances, therapies antagonizing neonatal Fc receptor (FcRn) to prevent placental pathogenic antibody transfer are progressing to clinical trials. Notably, in mice with partial FcRn deficiency, or more importantly with FcRn blockade, considerable effectiveness was demonstrated in treating models of fetal and neonatal immune thrombocytopenia purpura 236 , 237 , anti-NMDA receptor encephalitis 238 and arthrogryposis multiplex congenita 239 . In the arthrogryposis multiplex congenita model, the administration of FcRn antagonist to pregnant dams infused with human acetylcholine receptor-specific antibodies resulted in nearly significant decreases in pathogenic antibodies in the dams, and a major decrease of these antibodies in the fetuses 239 .…”
Section: Fcrn Blockade In the Clinicmentioning
confidence: 99%
See 1 more Smart Citation
“…Such transfer occurs in alloimmune and IgG-mediated autoimmune diseases, and in these instances, therapies antagonizing neonatal Fc receptor (FcRn) to prevent placental pathogenic antibody transfer are progressing to clinical trials. Notably, in mice with partial FcRn deficiency, or more importantly with FcRn blockade, considerable effectiveness was demonstrated in treating models of fetal and neonatal immune thrombocytopenia purpura 236 , 237 , anti-NMDA receptor encephalitis 238 and arthrogryposis multiplex congenita 239 . In the arthrogryposis multiplex congenita model, the administration of FcRn antagonist to pregnant dams infused with human acetylcholine receptor-specific antibodies resulted in nearly significant decreases in pathogenic antibodies in the dams, and a major decrease of these antibodies in the fetuses 239 .…”
Section: Fcrn Blockade In the Clinicmentioning
confidence: 99%
“…Notably, in mice with partial FcRn deficiency, or more importantly with FcRn blockade, considerable effectiveness was demonstrated in treating models of fetal and neonatal immune thrombocytopenia purpura 236 , 237 , anti-NMDA receptor encephalitis 238 and arthrogryposis multiplex congenita 239 . In the arthrogryposis multiplex congenita model, the administration of FcRn antagonist to pregnant dams infused with human acetylcholine receptor-specific antibodies resulted in nearly significant decreases in pathogenic antibodies in the dams, and a major decrease of these antibodies in the fetuses 239 . Therefore, in the setting of passive immunity, FcRn blockade might be especially effective as it could lead to a decline of pathogenic antibodies in the fetus not only via inhibition of FcRn-mediated transcytosis but also via their FcRn-mediated maternal and fetal recycling.…”
Section: Fcrn Blockade In the Clinicmentioning
confidence: 99%
“…10 Such detrimental effects of diaplacentally transferred antineuronal autoantibodies have previously been shown in experimental transfer models of human autoantibodies against N-methyl-D-aspartate (NMDA) receptors, 11 contactinassociated protein 2 (CASPR2), 12 aquaporin 4, 13 and acetylcholine receptors. 14 In contrast, developmental abnormalities caused by diaplacentally transferred synapsin-I autoantibodies were not studied so far. Here, we investigated, in an exploratory study, the prevalence of synapsin-I autoantibodies in pregnant women and analyzed their association with fetal development.…”
Section: Introductionmentioning
confidence: 99%
“…In the July and November 2021 issues of N2 , 2 experimental animal models of antibody-mediated diseases examined whether blockade of the FcRn to prevent the placental transfer of pathogenic antibodies decreased the likelihood of maternal antibody-mediated neonatal disease in the offspring. 15 , 16 One of the studies examined the effect of FcRn blockade in a model of maternal-to-fetal transfer of AChR antibody–mediated arthrogryposis multiplex congenita, and the other model was focused on the placental transfer of NMDAR antibody–mediated synaptic and behavioral alterations. 16 Although each model used a different antibody to block FcRn function, both studies showed that FcRn blockade prevents placental transfer of pathogenic antibodies and therefore the corresponding peripheral or CNS alterations.…”
mentioning
confidence: 99%